Laboratory Set-up Design for Testing Vibration Suppression Algorithms with Time Delays - Pilbauer, Dan; Bušek, Jaroslav; Kučera, Vladimír; Vyhlídal, Tomáš (Sborník vědeckých prací Vysoké školy báňské--Technické univerzity Ostrava. Řada strojní, 2014)
Vibrations occur in wide field of application in mechanical engineering hence developing new and advanced algorithms is useful. For practical verification of theoretical control algorithms it is necessary not only to simulate them, but also to test them in laboratory conditions at least. This article describes design of multipurpose laboratory set-up for testing active vibration control algorithms which consists of series of carts connected to each other on linear guides. Carts are equipped with accelerometers and position sensors for feedback control. Linear electric motors on the carts are used for suppressing vibration. The laboratory set-up is controlled by Matlab/Simulink via DAQ card connected to PC. Next to the set-up itself, two control algorithms intended for testing are presented in this article. First, principle of algorithm of resonator absorber with delayed acceleration feedback is described. Furthermore algorithm using input shaping for pre-compensating the oscillatory modes of the system is presented. By adding time delays into closed loop it becomes an infinite dimensional and in this case different approach than in conventional methods is needed. Finally some successful simulation results are presented as a part of practical experiment preparation.